Art Struggles: Confronting Internships and Unpaid Labour in Contemporary Art - Panos Kompatsiaris (tripleC: Communication, Capitalism & Critique, 2015)
This article explores the practices of recently formed and mainly UK-based art workers’ collectives against unpaid internships and abusive work. The modes through which these collectives perform resistance involve activist tactics of boycotting, site-specific protests, counter-guides, and whistleblowing and name and shame approaches mixed with performance art and playful interventions. Grappling with the predicaments of work in contemporary art, a labouring practice that does not follow typical processes of valorization and has a contingent object and an extremely loose territorial unity, this article argues that while the identity of the contemporary artist is systemically and conceptually moving towards fluidity and open-endedness, these groups work to reaffirm a collective in whose name it is possible to advance certain claims, assumptions, and demands. The contradictions and dynamics of art workers organizing against internships and voluntary work within a highly individualized, self-exploitative, and often privileged field are useful for informing labour organizing in the framework of ongoing capitalist restructuring.